The Universal Relation of Galactic Chemical Evolution: The Origin of the Mass-Metallicity Relation - Zahid, H. Jabran (2014)
We examine the mass–metallicity relation for z ≲ 1.6. The mass–metallicity relation follows a steep slope with a turnover, or "knee," at stellar masses around 1010 M☉. At stellar masses higher than the characteristic turnover mass, the mass–metallicity relation flattens as metallicities begin to saturate. We show that the redshift evolution of the mass–metallicity relation depends only on the evolution of the characteristic turnover mass. The relationship between metallicity and the stellar mass normalized to the characteristic turnover mass is independent of redshift. We find that the redshift-independent slope of the mass–metallicity relation is set by the slope of the relationship between gas mass and stellar mass. The turnover in the mass–metallicity relation occurs when the gas-phase oxygen abundance is high enough that the amount of oxygen locked up in low-mass stars is an appreciable fraction of the amount of oxygen produced by massive stars. The characteristic turnover mass is the stellar mass, where the stellar-to-gas mass ratio is unity. Numerical modeling suggests that the relationship between metallicity and the stellar-to-gas mass ratio is a redshift-independent, universal relationship followed by all galaxies as they evolve. The mass–metallicity relation originates from this more fundamental universal relationship between metallicity and the stellar-to-gas mass ratio. We test the validity of this universal metallicity relation in local galaxies where stellar mass, metallicity, and gas mass measurements are available. The data are consistent with a universal metallicity relation. We derive an equation for estimating the hydrogen gas mass from measurements of stellar mass and metallicity valid for z ≲ 1.6 and predict the cosmological evolution of galactic gas masses.